(untitled) (Comprehensive Journal of Science, 2025)
This study presents a graphical and analytical evaluation of electrical energy consumption using conventional electricity meters and prepaid (smart) meters. A representative sample of both meter types was selected, and consumption data were recorded during two distinct time periods (9:00 a.m. and 9:00 p.m.). These readings were systematically analyzed to obtain realistic and reliable results that reflect actual consumption patterns .. The study aims to provide a clear and comprehensive assessment of conventional and prepaid (smart) metering systems. It examines the electricity consumption behavior of residential subscribers during morning and evening periods, identifies the time period with the highest energy demand, and compares residential electricity consumption under the conventional billing system with that of the prepaid system . Based on an analysis of the General Electricity Company Decision No. (92) of 2023 concerning residential electricity tariffs, which sets the tariff at 40 dirhams, the study finds that this tariff category is applied to conventional meters. In contrast, under the prepaid system, residential consumption linked to bank installments or salary-based payments is charged at a tariff of 25 dirhams. The results indicate that electricity consumption recorded by conventional meters is higher than that recorded by prepaid meters. Additionally, electricity consumption during the evening period is significantly higher than during the morning period . Accordingly, the study recommends expanding the adoption of prepaid metering systems, issuing specific regulations by the General Electricity Company regarding prepaid electricity tariffs and peak demand periods, and gradually replacing conventional meters with prepaid (smart) meters .